Hubungan Beban Kerja Fisik dan Mental Perawat dengan Patient Safety di RSU Baitul Hikmah Kendal - Yuli Dwi Setyorini; Sri Wahyuni; Apriliani Yulianti (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
This study examines the relationship between nurses’ physical and mental workload and the implementation of patient safety at Baitul Hikmah General Hospital Kendal in 2025. Patient safety is a critical component of healthcare quality, and nurses, as the front-line providers, are directly involved in ensuring that safety standards are consistently maintained. However, high job demands often contribute to both physical and mental workload, which may affect compliance with patient safety practices. The research employed an analytical survey design with a cross-sectional approach, involving a total of 55 nurses from the emergency and inpatient units, selected using a total sampling technique. Data were collected through structured questionnaires assessing physical workload, mental workload, and adherence to patient safety procedures. Descriptive results showed that most respondents were in their productive age group, held a Diploma in Nursing, and had more than five years of clinical experience. The inferential analysis revealed a significant relationship between physical workload and patient safety (p-value = 0.023), whereas no significant relationship was found between mental workload and patient safety (p-value = 0.089). These findings suggest that while physical workload has a measurable impact on the implementation of patient safety, non-physical factors such as emotional maturity, professional responsibility, and coping strategies may play a more crucial role in ensuring safe and effective patient care. The study highlights the need for hospital management to address workload distribution and strengthen supportive measures that enhance nurses’ resilience and adherence to patient safety standards.